Studi Kelayakan Pengembangan PTC Indrapura Menjadi RSU Indrapura Dengan Pendekatan Analisis Kecenderungan (Analisis SWOT) - Daniel Ginting; Nina Fentiana (Universitas Batanghari Jambi, 2020)
The Indrapura Provincial Training Center (PTC) in Sipare-pare, Air Putih District, Batubara Regency was previously an educational facility for prospective doctors, nurses and midwives from various regions in North Sumatra. Since 2017 PTC Indrapura has been the UPT of Indrapura Hospital. The North Sumatra Provincial Government plans the UPT Indrapura Hospital to fully operate into a class C hospital based on the Decree of the Head of the Provincial Health Office Number: 441/10465/2017 dated 3 May 2017. The planning of the UPT Indrapura Hospital has a positive impact on the people in Batubara Regency. For this, a feasibility study is needed to avoid a wasted investment because the investment carried out can be different from the wants and needs of the community. Data analysis using secondary data, library research and field observations. The results of the feasibility diagram are Quadrant I: SO = 3.8 x 1.8 = 6.84; Quadrant II: WO = 2.4x 1.8 = 4.32; Quadrant III: ST = 3.8 x 2.5 = 9.50; Quadrant IV: WT = 2,4 x 2,5 = 6. The above facts show that the UPT Indrapura Hospital is in Quadrant III this means: The UPT Indrapura Hospital is feasible to be developed, with recommendations to strengthen strength and get opportunities.